Diagnosis experience of traction engines of locomotives - Ngoulou-A-Ndzeli; V. Yu. Tetter; V. G. Shakhov (Омский научный вестник)
Authors propose a method and algorithms for the rapid diagnosis of locomotives traction engines based on duplication of main frequency channel by additional wavelet analysis and decision — making on the methodology of fuzzy logic. The method and corresponding algorithms are uses for programming controllers of vibrodiagnostic systems.